Pengembangan Spiritualitas melalui Dakwah Majlis Dzikir An Nawawi Cilenggang - Merdeka, Muhamad; Amaliyah, Amaliyah (Perhimpunan Sarjana Ekonomi dan Bisnis, 2024)
The spirituality dimension is an important dimension in the management framework for worldly orientation and efforts to get closer to God. Efforts to fulfill the dimensions of spirituality require preachers who are able to preach and have good management. Portrait of the Prophet's da'wah as the greatest da'i of all the time, namely by using 3 methods of da'wah, namely: da'wah bil hal, da'wah bil verbal, and da'wah bil qolam. Including the principles of da'wah, both in the context of Sharia, the context of education, the context of development, the aim of da'wah at the dzikir an Nawawi assembly, as a means to strengthen and deepen the faith and piety of Muslims in the application of norms and values ​​in society, using four concepts of da'wah in a circle that is not disconnected, between verbal da'wah, bil qolam, bil hikmah, bil hal. Through individual, family and community approach programs. With the concept of Majlis dhikr an Nawawi, it is hoped that it will be able to develop the spirituality that society needs with the complexity of life they face.